2017
DOI: 10.1007/s13167-017-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of suboptimal health status as a potential risk assessment for type II diabetes mellitus: a case-control study in a Ghanaian population

Abstract: Due to a paradigm shift in lifestyles, there is growing concern that type 2 diabetes mellitus (T2DM) will reach epidemic proportions in Ghana. However, specific characteristics of the disease are under explored in this region. More challenging are those yet to be diagnosed or who complain of poor health in the absence of a diagnosed disease-suboptimal health status (SHS). We conducted a study to examine various factors that characterise SHS and T2DM. Using a cross-sectional design, we recruited 264 people as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 49 publications
1
70
0
Order By: Relevance
“…5 Although several items of SHS are similar to some diseases, SHS cannot reach the diagnosable condition of any current defined diseases. [3][4][5][6] A cross-sectional study conducted among workers in urban Beijing demonstrated that SHS was associated with cardiovascular risk factors. [3][4][5][6] A cross-sectional study conducted among workers in urban Beijing demonstrated that SHS was associated with cardiovascular risk factors.…”
mentioning
confidence: 99%
“…5 Although several items of SHS are similar to some diseases, SHS cannot reach the diagnosable condition of any current defined diseases. [3][4][5][6] A cross-sectional study conducted among workers in urban Beijing demonstrated that SHS was associated with cardiovascular risk factors. [3][4][5][6] A cross-sectional study conducted among workers in urban Beijing demonstrated that SHS was associated with cardiovascular risk factors.…”
mentioning
confidence: 99%
“…Suboptimal Health Status Questionnaire-25 (SHSQ-25) is the most widely used scale for measurement of SHS [7,8], which has been used in Africans, Asians and Caucasians [5]. Accumulating evidences indicated the associations between SHS and a wide range of diseases including mental disorders [9,10], psychosocial stress [11], obsessive-compulsive symptom and depression symptom [12], hypercholesterolemia [13], overweight and obesity [14], stroke [15,16], type II diabetes and cardiovascular disease [17]. All these diseases are related to the development of dementia.…”
Section: Health Transitions In Chinamentioning
confidence: 99%
“…The condition of SHS was measure by the questionnaire SHSQ-25 ( Table S1 in the Online Supplementary Document). The SHSQ-25 includes 25 items on five dimensions: 1) fatigue, 2) cardiovascular system, 3) digestive tract, 4) immune system and 5) mental health [12,17]. According to how often respondents experienced symptoms in the previous three months, each item was presented in a specific form on a Likert scale on a five-point scale.…”
Section: Shs Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, it encapsulates questions that comprehensively capture multiple indicators of good health, including fatigue, the cardiovascular system, the immune system, mental status and digestive tract (6,9,11). When completed, SHSQ-25 can reveal individuals who may be experiencing poor health that cannot be traced to a particular disease, referred to as Suboptimal Health Status (SHS) (6,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%